(3Gdbhd GdeCfhS HTQM HYV CdaGX GdbGehSs - (3HOQ GdOjf eMeO Hf jMji Hf YeQ GdbQGai GdeGdcjs; (3eMeO Hf jYbhH Hf eMeO, eLO GdOjf GdajQhRGHGOj,J (B817 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Rjf ef CQGO HGdJMdi HCTQa GddZGJ HYO , adG jNai Cf Yde GddZI ef CTQa GdYdhe hcGf ef CYXe eG Ufa ajg cJGH GdbGehS GdeMjW s
(3BNQgG (B:s
(3aWQH GdMGVQhf EdG GdeHQO aYLH efg QH GdefRd aXffi dMfJ aWQH GdeHQO ef gPG GdLhGH MJi Tb KhHg GfJgi eG JjSQ LeYg ef GdahGFO GdTQjaI hGdaQGFO GddWjaI s
(3cJHJ GdfSNI ai MjGI GdeDda hYfhGf GdfSNI HNWgs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B147s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B- (3U (B184 s
Keywords: (3GddZIs